How Should I Read These? : Native Women Writers in Canada - Hoy, Helen, 1949- (Book collections on Project MUSE., 2001)
"One of the few books on contemporary Native writing in Canada, Halen Hoy's absorbing and provocative work raises and addresses questions around 'difference' and the locations of cultural insider and outsider in relation to texts by contemporary Native women prose writers in Canada. Drawing on postcolonial, feminist, poststructuralist, and First Nations theory, it explores the problems involved in reading and teaching a variety of works by Native women writers from the perspective of a cultural outsider. In each chapter, Hoy examines a particular author and text in order to address some of the basis theoretical questions of reader location, cultural difference, and cultural appropriation, finally concluding that these Native authors have refused to be confined by identity categories such as 'women' or 'Native' and have themselves provided a critical voice guiding how their texts might be read and taught." "Hoy has written a thoughtful and original work, combining theoretical and textual analysis with insightful and witty personal and pedagogical narratives, as well as poetic and critical epigraphs - the latter of which function as counterpoint to the scholarly argument. The analysis is self-reflective, making issues of difference and power ongoing subjects of investigation that interact with the literary texts themselves and render the readings more clearly local, partial, and accountable. This highly imaginative volume will appeal to Canadianists, feminists, and the growing number of scholars in the field of Native studies."--Jacket.